PENDAMPINGAN OPTIMALISASI MARKETPLACE BAGI PELAKU UMKM UNTUK MENINGKATKAN PENJUALAN ONLINE - Handayani, Puspita; Ratnasari, Fina; Haryoso, Gunung Subagyo Anom (Fokus ABDIMAS, 2025)
This community engagement initiative was designed to support MSMEs in Cibadung Village, Gunung Sindur District, in addressing obstacles related to digital marketing and the underutilization of online marketplaces. Adopting a structured approach, the program offers digital literacy workshops, guidance on optimizing online stores, training in digital marketing techniques, inventory control, customer service enhancement, and regular monitoring and evaluation. The involvement of students as mentors fosters stronger collaboration between academia and entrepreneurial practice. The program’s outcomes indicate improvements in the digital skills of MSMEs, growth in sales transactions, and enhanced competitiveness of local products in the online marketplace. With its systematic and sustainable approach, this program has the potential to serve as a replicable model for digital empowerment of MSMEs in other areas.